Daily field checking list by Walter Rosene, April 23, 1941 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Daily field checking list of birds observed by Walter Rosene, Robert Walker, Bruce Fleming Stiles, and Council Bluffs Bird Club, April 23, 1941. Plustek--flatbed